First record of Pagiocerus frontalis (Fabricius) (Coleoptera: Curculionidae: Scolytinae) in stored maize in Africa - Chidege, Maneno Y.; Ndakidemi, Patrick A.; Venkataramana, Pavithravani B. (Zootaxa, 2026)
Tanzanian smallholder farmers typically sell maize soon after harvest to avoid storage losses, but emerging pests threaten post-harvest systems and food security. The bark beetle Pagiocerus frontalis (Fabricius) (Coleoptera: Curculionidae: Scolytinae), a pest of maize and avocado seeds, is reported here for the first time in Africa. First detected in December 2018 on stored provitamin-A maize (CP201) in Arusha, Tanzania, its identity was confirmed through morphological characteristics, feeding behavior, and COI sequence analysis, which revealed close similarity to populations from Mexico and Panama. Pagiocerus frontalis caused severe damage to stored maize grain and to avocado seeds in our preliminary rearing trials. The species also demonstrated the ability to infest multiple maize varieties. Its impacts resemble those of the Prostephanus truncatus (Horn) (Coleoptera: Bostrichidae), which caused severe grain losses following its introduction to Africa. Early detection and identification of P. frontalis are therefore critical to mitigate this emerging threat to African food security.